2019
DOI: 10.1002/pssb.201800610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microwave Excitation‐Power on the Narrow Negative Magnetoresistance Effect Around B = 0 T in the Ultra‐High Mobility GaAs/AlGaAs 2DES

Abstract: In addition to the photo-excited zero-resistance states and radiation-induced magnetoresistance oscillations, which can be observed in the high-quality GaAs/AlGaAs two-dimensional electron system (2DES), magnetotransport studies of this 2DES also exhibit interesting dark magnetoresistance effects. Here, a narrow negative magnetoresistance (MR) effect that appears around zero field, and spans over about À0.02 T B 0.02 T is examined. This experimental work aims to study the influence of microwave (MW) photoexcit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In addition to the photo-excited effects, the dark magneto-transport properties including positive magnetoresistance 51,52 , giant negative magnetoresistance [53][54][55][56][57][58][59][60][61] , and narrow negative magnetoresistance effect near zero field have also attracted recent experimental attention. So far as the larger negative giant magneto-resistance is concerned, recent studies have shown remarkable features such as size dependence, tunability with supplemental dc-current, and coexistence with-and separability from-radiation induced magnetoresistance oscillations [59][60][61][62][63][64][65] . One emerging theory suggests that some of the observed features of the larger negative giant magnetoresistance effect could be a signature of a viscous electron liquid in the low magnetic field quasi ballistic transport regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the photo-excited effects, the dark magneto-transport properties including positive magnetoresistance 51,52 , giant negative magnetoresistance [53][54][55][56][57][58][59][60][61] , and narrow negative magnetoresistance effect near zero field have also attracted recent experimental attention. So far as the larger negative giant magneto-resistance is concerned, recent studies have shown remarkable features such as size dependence, tunability with supplemental dc-current, and coexistence with-and separability from-radiation induced magnetoresistance oscillations [59][60][61][62][63][64][65] . One emerging theory suggests that some of the observed features of the larger negative giant magnetoresistance effect could be a signature of a viscous electron liquid in the low magnetic field quasi ballistic transport regime.…”
mentioning
confidence: 99%
“…A brief report on our early work appears at ref. 63 . Here, we present data as a function of several parameters, and subject the observed narrow negative magnetoresistance data to an empirical fit in order to extract the characteristic lengths.…”
mentioning
confidence: 99%